Democratic Republic of Congo Systematic Country Diagnostic : Policy Priorities for Poverty Reduction and Shared Prosperity in a Post-Conflict Country and Fragile State - World Bank Group (World Bank, Washington, DC, 2018)
The Democratic Republic of the Congo (DRC) is a classic example of the paradox of plenty, since the country is extremely rich in natural resources while its population is extremely poor. It is the largest country in Sub-Saharan Africa (SSA) with a total surface area of about 234 million hectares (equivalent to the size of Western Europe). Poverty in the DRC remains pervasive, and greater than the SSA average. About two-thirds of the population lives below the poverty line. Chapter 2 of the systematic country diagnostic (SCD) shows that between 2005 and 2012 the proportion of people living below the poverty line declined from 69.3 percent to 64 percent, respectively. Demographic trends, reinforced by gender discrimination and lack of social policies, contributed to maintaining poverty at relatively high levels. The poor state of infrastructure is a major constraint on sustainable and inclusive growth in the country. The country’s weak institutions failed to build the foundations of a resilient economy and absorb external shocks, hence exposing the society to cycles of violence and impoverishment. The report identifies five major emerging opportunities and priority areas where policy actions can provide quick wins and build cumulative and virtuous cycles to sustain inclusive growth and foster resilience and shared prosperity over the next decade: (1) building the resilience of the macroeconomic framework; (2) building inclusive institutions and strengthening governance; (3) leveraging natural resources, infrastructure, and agriculture; (4) building human capital; and (5) leveraging the private sector by effectively implementing investment climate reforms, and strengthening institutions that support markets.